MCQs in biochemistry. Module 2. Submodule 4: Biochemistry of vitamins. functional biochemistry of organs and tissues. biochemical indexes of blood and urine in diagnostics of metabolic disorders - Krisanova, N. V.; Ivanchenko, D. G.; Aleksandrova, K. V.; Rudko, N. P.; Крісанова, Наталія Вікторівна; Іванченко, Дмитро Григорович; Александрова, Катерина Вячеславівна; Рудько, Наталія Петрівна (Zaporozhye state medical university, 2015)
This book has been compiled with main aim to help the II year students of International Faculty to prepare in systematic way to control testing on submodule 4 of module 2. It contains more than 304 original MCQs. The book is well balanced and consists of multiple choice questions from all the important topics like: the role of vitamins in the metabolic processes of humans; biochemistry of muscular, connective and nervous tissues, xenobiotics metabolism and other important biochemical aspects. This book is recommended to all the students preparing for each class and control testing on submodule 4 of module 2.